Human African trypanosomiasis & heart. (1st December 2020) - Ortiz, Hector Isaac Alejandro; Farina, Juan Maria; Saldarriaga, Clara; Mendoza, Ivan; Sosa Liprandi, Alvaro; Wyss, Fernando; Burgos, Lucrecia Maria; Alexander, Bryce; Baranchuk, Adrian
ABSTRACT: Introduction: Human African Trypanosomiasis is a neglected tropical disease resulting from the infection with the parasite Trypanosoma brucei. Neurological compromise often dominates, and the impact of cardiovascular involvement has not been fully investigated. Recently, publications indicate that cardiovascular compromise is more frequent than previously thought. Early detection of cardiac complications may be of utmost importance for healthcare teams. Area covered: As a part of the 'Neglected Tropical Diseases and other Infectious Diseases involving the Heart' (the NET-Heart Project), the purpose of this article is to review all the information available regarding cardiovascular implications of this disease, focusing on diagnosis and treatment, and proposing strategies for early detection of cardiac manifestations. An electronic systematic literature review of articles published in MEDLINE, PubMed and EMBASE was performed. From 50 initial studies, 18 were selected according to inclusion criteria. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses statement was used for conducting and reporting this review. Expert opinion: Cardiovascular compromise through infiltrative and inflammatory mechanisms seems to be frequent, and includes a wide spectrum of severity. Conventional 12-lead electrocardiogram could be a useful test for screening cardiovascular manifestations and used as a guide for considering specific treatments or more sophisticated diagnostic tools.